Mirroring Treatment dalam Perspektif Kristen: Pembentukan Karakter Melalui Teladan Yesus - Hendri Hendri (Sekolah Tinggi Teologi Bethel Ambon, 2025)
This article examines the concept of Mirroring Treatment from a Christian perspective as a theological approach to character formation through the Word of God, the example of Jesus Christ, and the work of the Holy Spirit. This study employs a qualitative method with a library research approach through the analysis of biblical texts and relevant theological literature. The findings reveal that humanity was originally created in the image and likeness of God to reflect His character fully. However, the fall into sin damaged this reflective function, causing humans to reflect sinful nature rather than the character of God. Through the Word of God as a spiritual mirror, individuals become aware of their sinful condition and are called to repentance and renewal. Jesus Christ becomes the primary model and standard in this restorative process, while the Holy Spirit transforms believers progressively into the likeness of Christ. This study concludes that Christian Mirroring Treatment is not merely a form of psychological reflection or moral improvement, but a Christ-centered and continuous spiritual transformation process in Christian character formation.